Mushroom intake and depression: A population-based study using data from the US National Health and Nutrition Examination Survey (NHANES), 2005–2016 - Ba, Djibril M.; Gao, Xiang; Al-Shaar, Laila; Muscat, Joshua E.; Chinchilli, Vernon M.; Beelman, Robert B.; Richie, John P. (Journal of affective disorders, 2021)
•Association between mushroom intake and depression was examined using NHANES.•The overall prevalence of depression was 5.9%.•Participants with mushroom consumption had lower odds of having depression. Mushrooms contain numerous bioactive compounds that may be associated with reduced anxiety including vitamin B12, nerve growth factor, antioxidants, and anti-inflammatory agents. We hypothesized that mushroom consumption is associated with a lower risk of depression in American adults. Data from the National Health and Nutrition Examination Survey 2005–2016 was used. Up to two days of 24 h dietary recall were analyzed to assess mushroom intake frequency. Depression was measured using the Patient Health Questionnaire (PHQ-9, score ≥ 10). We used multivariable logistic regression models, adjusting for potential confounding factors. Among 24,699 participants (mean (SE) age: 45.5 (0.3) years), the weighted prevalence of depression was 5.9%. Mushrooms were consumed by 5.2% of participants. Compared with the lowest tertile of mushroom intake, participants in the middle tertile (median intake = 4.9 g/d, number of cases = 16) had lower odds of depression (adjusted OR = 0.31; 95% confidence interval [CI] 0.16, 0.60) while those in the highest tertile did not differ (median intake = 19.6 g/d, adjusted OR = 0.91; 95% CI: 0.47, 1.78, number of cases = 22) (P-trend = 0.42). Cross-sectional data and lack of information on specific types of mushrooms consumed. Mushroom consumers had a lower odd of depression. However, we did not observe a dose-response relationship.